2014
DOI: 10.1155/2014/109303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermostability of a Fungal Alkaline Protease by Different Additives

Abstract: A fungal strain (Conidiobolus brefeldianus MTCC 5184) isolated from plant detritus secreted a high activity alkaline protease. Thermostability studies of the fungal alkaline protease (FAP) revealed that the protease is stable up to 50°C with 40% residual activity after one hour. Effect of various additives such as sugars, sugar alcohols, polyols, and salts, on the thermostability of FAP was evaluated. Among the additives tested, glycerol, mannitol, xylitol, sorbitol, and trehalose were found to be very effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…We also found that the thermostability of both AprA and AprA-PPC was also significantly improved by the addition of Ca 2+ . Similar results were also observed for several alkaline proteases from organisms such as B. lehensis 16 , B. pumilus 57 , A. oryxae 81 , S. koyangensis 25 , and Conidiobolus brefeldianus 79 . Ca 2+ is considered to effect protease thermostability by strengthening the intramolecular interactions of the enzyme and by binding of Ca 2+ to autolysis sites 79 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also found that the thermostability of both AprA and AprA-PPC was also significantly improved by the addition of Ca 2+ . Similar results were also observed for several alkaline proteases from organisms such as B. lehensis 16 , B. pumilus 57 , A. oryxae 81 , S. koyangensis 25 , and Conidiobolus brefeldianus 79 . Ca 2+ is considered to effect protease thermostability by strengthening the intramolecular interactions of the enzyme and by binding of Ca 2+ to autolysis sites 79 .…”
Section: Discussionsupporting
confidence: 82%
“…Ca 2+ and other divalent ions such as Mn 2+ and Mg 2+ represent additional factors known to increase protease activity and thermostability 65 , 79 . Our current study showed that both AprA and AprA-PPC were activated by Ca 2+ , Mn 2+ , and Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For peptidase application, the protein structural stability is a crucial biochemical property favoring its feasibility for commercial use. Enzymes are susceptible to denaturation by different physicochemical agents, including deamination, proteolysis, oxidation, inhibition, and structural changes due to pH and temperature [82][83][84][85][86].…”
Section: Microorganism and Peptidase Productionmentioning
confidence: 99%
“…Higher thermal stability is one of the fundamental requirements for the application of an enzyme in industrial processes; it increases the efficiency of enzyme. Therefore, searching for thermostable enzymes or improve the thermostability of enzymes has been the priority for researchers over the years (Nirmal and Laxman, 2014). The factors affecting thermostability are important for understanding the functions of proteins and their use in various industries (Ruller et al, 2008).…”
Section: Thermostable Xylanase and Its Propertiesmentioning
confidence: 99%